Representasi Keimanan dalam Penanggulangan Hate Speech: Analisis Tematik atas Hadis Ujaran Kebencian - Nofiyanti, Fitria; Friyadi, Arif (el Buhuth: Borneo Journal of Islamic Studies, 2025)
The purpose of this article is to analyze expressions of faith in responding to hate speech through a thematic analysis of selected hadiths that emphasize the importance of ethical discourse as a basis for action on social media. Qualitative approach was used in this research, using documentation and contextual analysis of primary hadith sources, tafsir, and related literature. The findings reveal three main points: first, the quality of an individual’s speech is strongly correlated with their level of faith as taught in the hadiths; second, the social context of pre-Islamic Arab society, which was filled with verbal aggression, underscores the urgency of the Prophet Muhammad’s prohibition of hate speech; third, true faith is manifested in polite verbal behavior, while hate speech indicates weak faith and the potential for social division. This understanding is relevant to contemporary digital communication and affirms that the internalization of ethical speech based on hadith should serve as a foundation in education, preaching, and public policy. Overall, this study highlights that maintaining ethical communication is an integral part of strengthening faith and fostering a civilized society.